Sovereign debt - Jörn Quitzau; Christopher Prömel; Henning Vöpel; Maike Cotterell (Berenberg Bank und Hamburgisches WeltWirtschaftsInstitut (HWWI), 2019)
[Introduction] Ten years ago, the global economic and financial crisis was at its peak. When ailing investment bank Lehman Brothers filed for insolvency on 15 September 2008, the smouldering crisis on the financial markets became a full-scale firestorm. While falling real estate prices had already been causing problems for banks and other financial institutions, it was the Lehman collapse that fanned the flames of the disaster. The consequences were devastating. In several industrial countries, bank after bank was plunged into financial turmoil, and several had to be propped up by the state. The global economy was upended, with many companies and consumers cutting back on spending because of concerns about the consequences of the crisis on the financial markets. Growth in Germany collapsed by roughly 5%, something that had never before been seen in the post-war era. Governments around the world drew up extensive economic stimulus packages in a bid to counter the collapse of private sector spending. Central banks responded with drastic interest cuts, thus laying the foundations for an ultra-expansive monetary policy that would persist for several years. With the economic stimulus measures and the direct aid for troubled financial institutions (including nationalisation), national governments took on a heavy financial burden. Parts of what had been private debt were converted into public debt. The resulting dramatic rise in sovereign debt, which in some cases had already been running at a high level, caused many market participants and the general public to fear huge inflation, state bankruptcy and even currency reforms. A large number of observers described the situation as hopeless. It was this widespread concern that prompted us, back in 2009, to take an in-depth look at the topic of sovereign debt as part of our Strategy 2030 series. The tenor of our analysis at the time was that while the situation in the financial system and with public finances was very serious, there were ways out of the crisis without having to resort to the state bankruptcies, currency reforms or hyperinflation that people feared. Ten years on, we now know that these doomsday prophecies did not come true. With the exception of Greece, there were no state bankruptcies. Similarly, there was no need for currency reforms. Even the euro, which suffered a severe loss of trust in the interim, did not implode. And there has still not been any significant consumer price inflation in the major industrial countries. In fact, in recent years central banks have been more concerned with preventing deflation. So is this positive outcome merely a »snapshot« of the current moment in time, or is there good reason to suggest that we have weathered the crisis? Is there a risk that these painstakingly achieved successes in stabilising state finances could be lost again the next time the economy takes a nose-dive? What happens if interest rates one day start to spike? And is there a threat of a new debt crisis if highly indebted countries such as Italy destroy the tediously crafted reform successes with another departure in economic policy? These are the questions we want to examine in this study. We will shed some light on the status quo and outline the areas that could pose new risks with the ability to reignite the debt crisis.
Keywords: 330